PENGARUH PERMAINAN KOOPERATIF TERHADAP KEMAMPUAN SOSIAL ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK MUTTAQIN BANGKINANG KOTA - Artha, Rafika Septia; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aim to know the influence of cooperative game to social ability of 5-6 years old children at Taman Kanak-kanak Muttaqin Bangkinang Kota. Population of this research was Taman Kanak-kanak Muttaqin child’s, sample of research are 20 childs. Method of research was experiment which this research tries to look for this research aim to know the influence of cooperative game to social ability of 5-6 years old children at Taman Kanak-kanak Muttaqin Bangkinang Kota. Instrumental of this research used observation sheet. Data analysis tech used utilizes scale test-driving and statistical methods analysis with SPSS For's program ver's Windows 17. The result of this research that acquired available the influence of cooperative game to social ability of 5-6 years old children at Taman Kanak-kanak Muttaqin Bangkinang Kota. Obtained value t tabel with df 19 in taraf signifikansi 5% (2-tailed) of 2,093. This known t hitung (17,206)>t table (2,093) or signifikansi (0,000)<0,05. It has been suggested that there is a difference in the results between the pretest and posttest significant. It is shown from the correlation coefficient point (r ) as big as 0,687 by determinant coefficients (r 2 ) as big as 0,687 x 0,687 = 0,472 mean it is affecting cooperative game to social ability is as big as 47,2% one lie on medium category.Key Words : Social Ability, Cooperative Game